How the brain learns to read - Sousa, David A. (Corwin, 2014)
Examines source material on brain research and provides primary and secondary classroom reading strategies for teachers based on the most current findings. There are five core chapters on - what the research tells us, understanding language acquisition, instructional strategies, identifying reading problems, and strategies for resolving reading problems. The book includes a useful glossary of terms integrates brain diagrams to language acquisitions and strategies.